برصغیر میں اجتہادی فکر کا پس منظر (شاہ ولی اللہ کی کوششوں کے تناظر میں): Background of Ijtihadi Thought in the Subcontinent (In the Context of Shah Waliullah's Efforts) (Al-Aasar, 2025)
Since the purpose of Ijtihad is not to replace divine law with human law, but to make the Islamic legal system dynamic in line with the pace of time, Ijtihad holds a vital position in Sharia and in Islamic jurisprudence as the source of life. Ijtihad has such a deep connection with Islam and its characteristics that it will be impossible to deviate from it until the Day of Judgment. From the time of the Prophet Muhammad (PBUH) to the present day, the need for Ijtihad has always arisen in every era. Each person has continued the process of Ijtihad according to the needs and circumstances of their time. During the time of Shah Waliullah, when the Muslim community was facing a crisis of intellectual and jurisprudential differences, he guided the Muslim community out of the tangled forest of blind imitation, bias, and narrow-mindedness and led them onto a clear and transparent path of thought and reflection. He clarified the true nature of the excesses and deficiencies in the jurisprudential differences and established the correct position of the Mujtahids and their Ijtihads. This article will provide a brief overview of his Ijtihadi efforts